Causes and consequences of changing land tenure institutions in Western Ghana - Otsuka, Keijiro; Aidoo, J. B.; Tachibana, Towa; Quisumbing, Agnes R. (International Food Policy Research Institute, 1998)
Land tenure institutions in customary land areas of Sub-Saharan Africa have been evolving towards individualized ownership. Communal land tenure institutions aim to achieve and preserve the equitable distribution of land (and hence, income) among community members. Uncultivated forestland is owned by the community or village, and as long as forest land is available, forest clearance of forest is easily approved by the village chief. Forest clearance is usually rewarded by relatively strong individual rights to land, which are further strengthened by long-term or permanent improvements in the land. Land rights, however, tend to become weaker if land is put into fallow over extended periods. In communal ownership systems, individual rights to transfer and inheritance are limited and controlled by leaders of the extended family. Thus, incentives to invest in land resources under such land tenure rules may be weaker due to unclear and uncertain individual rights....Changes in mode of land acquisition. Based on a survey of 60 villages in Western Ghana, where cocoa is the dominant crop, this study identifies statistically the determinants and the consequences of changing customary land tenure institutions....Under increasing population pressure, shifting cultivation becomes unsustainable since gradual decreases in the fallow period reduce soil fertility. Under such conditions, more labor-intensive and land-saving farming systems must be established. In Western Ghana, customary land tenure institutions have evolved toward individualized systems in order to provide appropriate incentives to invest in tree planting and management.